PEMODELAN KAWASAN PASAR SOUVENIR DI DESA TOMOK (Objek Kasus : Desa Wisata Tomok, Kabupaten Samosir, Sumatera Utara) - Sitohang, Ida Nova; Pakpahan, Raimundus; Silitonga, Shanty (Unika Santo Thomas, 2019)
The tourist market or souvenir shop is a place of sale and purchase transactions in the tourist area that sells merchandise. The tourism market can be classified into traditional markets according to the physical, time, area of activities and goods traded. The tourism market can also be classified as a traditional market according to its function as culture, a market that has multi roles, not only acts as a meeting place between sellers and buyers but the market also has a function as a meeting place for each of those who use the market. Trading is one of the economic activities of the Tomok tourism village. The souvenir shop shows a lot of variants in terms of size / area, shape and ownership of the shop. It is importance to provide the right model in the souvenir market area in Tomok village. The research is using Modelling methodology. The benefit of this study is to find a model of the souvenir market area in Tomok tourism village that meets the souvenir market criteria.